2016
DOI: 10.1002/fsn3.356
|View full text |Cite
|
Sign up to set email alerts
|

Bambara–wheat composite flour: rheological behavior of dough and functionality in bread

Abstract: The rheological behavior and functional properties of doughs from bambarawheat composite flour was investigated. Bambara-wheat composite flour was prepared by substituting wheat with 0%, 10%, 15%, and 20% of bambara flour. The rheological behavior of their dough was analyzed with Mixolab. Breads produced from the flour were analyzed for physical characteristics. Organoleptic analysis was carried out by 20 panelists. Mixolab analysis revealed, except for stability time, depreciating values for dough consistency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 11 publications
4
24
0
Order By: Relevance
“…(a) Paste prepared from bambara groundnut flour, (b) snack prepared from bambara groundnut flour, (c) paste prepared from bambara groundnut seed, (d) snack prepared from bambara groundnut seed, (e) paste prepared from cowpea flour, (f) snack prepared from cowpea flour, (g) paste prepared from cowpea seed, and (h) snack prepared from cowpea seed (17.93%, 19.38%, and 20.23%, respectively) of bambara groundnut flour fortification, which could be associated with the high protein content (24.53 g/100 g) of the bambara groundnut flour used for the fortification. This result is in agreement with Erukainure et al (2016), who found significant improvement in the protein content of bread fortified with bambara groundnut. According to these authors, bread fortified with 15% of bambara groundnut flour inclusion was the most acceptable.…”
Section: Food Enrichment and Fortificationsupporting
confidence: 93%
“…(a) Paste prepared from bambara groundnut flour, (b) snack prepared from bambara groundnut flour, (c) paste prepared from bambara groundnut seed, (d) snack prepared from bambara groundnut seed, (e) paste prepared from cowpea flour, (f) snack prepared from cowpea flour, (g) paste prepared from cowpea seed, and (h) snack prepared from cowpea seed (17.93%, 19.38%, and 20.23%, respectively) of bambara groundnut flour fortification, which could be associated with the high protein content (24.53 g/100 g) of the bambara groundnut flour used for the fortification. This result is in agreement with Erukainure et al (2016), who found significant improvement in the protein content of bread fortified with bambara groundnut. According to these authors, bread fortified with 15% of bambara groundnut flour inclusion was the most acceptable.…”
Section: Food Enrichment and Fortificationsupporting
confidence: 93%
“…When heating begins during the mixing process, the dough loses its stability before reaching the minimum torque, C2. A signi cant di erence (p < 0.001) in C2 was found with respect to the milling method rather than the cultivar, indicating that WWFs milled by JM (0.54-0.56 Nm) had a more stable gluten structure during heating [50] than WWFs milled by HM (0.44-0.50 Nm). In the dough heating process, protein denaturation and unfolding were induced…”
Section: Dough Properties Of Wwfsmentioning
confidence: 92%
“…Sensory assessment is a vital measure for quality assessment in a newly developed food product to attract consumers and to meet their requirements [ 29 ]. The choice of a food product depends on various factors such as character, mood and experience, and attitudes like sensory properties, health and nutrition, and price and value [ 8 ]. The sensory attributes of pan and pita bread prepared from wheat flour supplemented with or without different concentrations of buttermilk are presented in Table 6 .…”
Section: Resultsmentioning
confidence: 99%